Deepening understanding of language through synaesthesia: a call to reform and expand - Mankin, Jennifer L. (Philos Trans R Soc Lond B Biol Sci, 2019)
In this paper, I present arguments and suggestions for the improvement of the scientific study of synaesthesia, and particularly grapheme-colour synaesthesia in relation to psycholinguistic research, although the principles I advocate can be easily adapted to any subfield of synaesthesia study. I postulate that the current state of research on synaesthesia in general, and on grapheme-colour synaesthesia in particular, suffers from a lack of exploratory evidence and essential groundwork upon which to build hypothesis-testing studies. In particular, I argue that synaesthesia research has been artificially bounded by assumptions about the nature of synaesthetic experiences, which constrain both the questions that researchers ask and the way in which they go about answering those questions. As a specific example, I detail how much of the current research on grapheme-colour synaesthesia is built to accommodate two major assumptions about the nature of colours for letters and for words—assumptions which I will contend are not universally true, and the exceptions to which point to a much richer and heterogeneous understanding of synaesthetic experience than current research practices capture. The top-down predetermination of what is important or meaningful to measure, and what is not, has subsequently impeded a full understanding of what synaesthesia is and how it works. I argue that these assumptions must be carefully addressed and evaluated, both for the particular case of grapheme-colour synaesthesia and for the field as a whole, to move towards a holistic and fruitful understanding of synaesthesia as a phenomenon and as a tool to study language, thought and perception. To that end, I propose specific recommendations for synaesthesia researchers to solidify and expand their understanding and to capture the actual experience of synaesthetes. This article is part of a discussion meeting issue ‘Bridging senses: novel insights from synaesthesia’.